The value of intra- and peri-tumor ultrasound-based radiomics in predicting lymph node metastasis of thyroid carcinoma - SHI Lin; ZHONG Lichang; MA Fang; GU Liping; ZONG Guo (Yixue xinzhi zazhi, 2025)
Objective To investigate the value of ultrasound-based intratumoral and peritumoral radiomics in predicting lymph node metastasis from primary thyroid cancer.Methods A retrospective collection of patient data from January 2016 to April 2023 at the Sixth People’s Hospital (Lingang Campus) in Shanghai was conducted for patients who underwent routine ultrasound examinations and were pathologically diagnosed with thyroid cancer. On the two-dimensional ultrasound images, the largest cross-sectional view of the lesion was selected to delineate the region of interest. This region was then automatically expanded by 2 mm outward to define the peritumoral area. Intratumoral and peritumoral radiomics were used to extract features. Pationts were randomly divided into training group and validation group in a 7 : 3 ratio. The least absolute shrinkage and selection operator algorithm was employed to select radiomic features. Multiple layer perceptron models were used to establish several predictive models: a clinical variable model, an intratumoral radiomics model, a peritumoral radiomics model, a combined intratumoral and peritumoral radiomics model, and a model that integrates radiomics features with clinical variables. Receiver operating characteristic curves and area under curve (AUC) were used to evaluate the model's prediction performance for lymph node metastasis.Results Among 280 cases of thyroid cancer, 102 cases (36.43%) had lymph node metastasis following surgical treatment. The patients were randomly divided into a training group of 196 cases and a validation group of 84 cases. Multivariate Logistic regression analysis reveals a notable correlation among patient age, thyroid peroxidase antibody, and the proximity of nodules to the thyroid capsule, with the occurrence of lymph node metastasis in thyroid cancer (P